Caracterização da fibra de co-produtos agroindustriais e sua avaliação nutricional para coelhos em crescimento - Retore, Marciana (2009)
Two experiments were carried out in Rabbit Laboratory of Animal Science Department at Federal University of Santa Maria, RS, where were studied the influence of different fractions of fiber from agricultural by-products (citrus pulp, soybean hulls, linseed bran and corn gluten meal) on performance, digestibility coefficients, blood parameters and meat quality of rabbits submitted to diets. The diets were isoproteic and isoenergetic, 18% of crude protein and 3,000 kcal/kg of digestible energy, respectively. Eight New Zealand White rabbits were utilized to each treatment, from 40 to 89 days of age. At the first experiment, the treatments were: AHcontrol diet, with alfalfa hay; CP- total substitution of alfalfa hay by citrus pulp and SH- total substitution of alfalfa hay by soybean hulls. The animals of the treatments CP and SH showed similar performance, carcass weight and carcass dressing percentage to the animals of the treatment AH. The DM, OM, CP and NDF apparent digestibility coefficients were superior for the diet SH, due to fiber quality. Reductions on triglycerides, cholesterol, hemoglobin and glucose levels were observed in the blood of the animals fed with citrus pulp, because of the high cation-exchange capacity of this by-product. Meat tenderness was higher for those animals that consumed the diet with soybean hulls, due to better nutrients digestibility. The different fiber fractions from citrus pulp and soybean hulls do not affect animals performance and weight and dressing carcass, showing that these ingredients can substitute the alfalfa hay on rabbits diet. Fiber quality of citrus pulp decrease animals blood triglycerides and cholesterol levels. The lower amount of lignin in relation to cellulose and hemicellulose of the soybean hulls provides better nutrients digestibility coefficients. At the second experiment the treatments were: AH- control diet, with alfalfa hay; LB- total substitution of alfalfa hay by linseed bran and GM- total substitution of alfalfa hay by corn gluten meal (20% of crude protein). The animals from GM treatment showed similar performance in relation to the ones from AH treatment, although the carcass dressing percentage did not differ among the byproducts. Linseed bran proportioned lower performance, due to higher fiber hydration capacity and gel formation. The DM, OM, CP and NDF apparent digestibility coefficients were superior for GM treatment, due to fiber quality. Meat tenderness was higher for those animals that consumed the diet of the treatment GM because of the better digestibility coefficients. Corn gluten meal can substitute alfalfa hay on rabbits diet. Linseed bran, due to high amount of soluble fiber and high hydration capacity, affects animal performance and meat tenderness.